2009
DOI: 10.1152/ajplung.00132.2009
|View full text |Cite
|
Sign up to set email alerts
|

Role of lung iron in determining the bacterial and host struggle in cystic fibrosis

Abstract: Cystic fibrosis (CF) is the most common lethal genetic disorder in Caucasian populations. It is a multiorgan system disease that affects the lungs, gastrointestinal tract, liver, and pancreas. The majority of morbidity and mortality in CF relates to chronic airway infection with a variety of bacterial species, commencing in very early infancy, which results in lung destruction and ultimately organ failure (41, 43). This review focuses on iron homeostasis in the CF lung and its role in determining the success a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 107 publications
(103 reference statements)
0
46
0
Order By: Relevance
“…While many factors can be anticipated to impact the ecological success of different species in the lung, one important parameter is competition for iron (59). In coculture experiments pitting Staphylococcus aureus against P. aeruginosa, it was found that in the presence of S. aureus, P. aeruginosa decreased transcription of genes known to be regulated by iron availability (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While many factors can be anticipated to impact the ecological success of different species in the lung, one important parameter is competition for iron (59). In coculture experiments pitting Staphylococcus aureus against P. aeruginosa, it was found that in the presence of S. aureus, P. aeruginosa decreased transcription of genes known to be regulated by iron availability (42).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the actual chemistry of iron in CF sputum is poorly defined and likely varies temporally for any given patient, from patient-to-patient, and within any given microenvironment. This is due to a complex set of interactions between the host and microbial cells, some of which are just beginning to be elucidated (23), that can affect the chemistry of iron and its release (59). That said, it is reasonable to assume that if lactoferrin is present in sufficient amounts to bind Fe(III) on mucosal surfaces, it would block biofilm formation at early stages of infection (5,68).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, the same group have shown that a combination of hypocyanite and lactoferrin enhances the ability of tobramycin and aztreonam to eliminate P. aeruginosa biofilms on lung epithelial cells (Moreau-Marquis et al, 2015). Data from Reid et al (2009) indicate that iron chelation enhances the efficacy of tobramycin therapy in a low oxygen environment, such as that which pertains in areas of the CF lung. Taken together, these data provide strong evidence for iron chelation to be an effective adjunctive therapy in treating P. aeruginosa lung infections.…”
Section: Novel Therapeutic Strategies Targeting Iron Acquisition In Cmentioning
confidence: 99%
“…Because steep chemical gradients can develop within biofilms over a small spatial scale (28), it is reasonable to expect that Fe(II) could exist in appreciable amounts in these microhabitats. Although the dominant iron oxidation state in the CF lung is unclear (44), it likely changes as infections progress and the local environment becomes increasingly reducing. On a related note, one reason to postulate that Fe(II) may be important for P. aeruginosa is that phenazines are known to be produced at micromolar concentrations in the CF lung (65).…”
mentioning
confidence: 99%